ABOLITION OF PARATE EXECUTIE AS A RESULT OF CONSTITUTIONAL COURT RULING NUMBER 18/PUU-XVII/2019 - Antonius Nicholas Budi (Jurnal Hukum dan Peradilan, 2020)
Constitutional Court Ruling Number 18/PUU-XVII/2019 have caused changes to the method of execution in fiduciary security rights, by introducing, through the Court Ruling’s third judgement, either voluntary or legal effort requirement to the acknowledgement of breach of contract in the exercise of parate executie. This is due to the Court having erred in considering parate executie as connected to executoriale titel. This paper first aims to delineate parate executie as a distinct method of foreclosure from executoriale titel using a conceptual approach. By further using this approach, this paper shows that the effect on foreclosure in fiduciary right is that executoriale titel is unaffected while foreclosure in parate executie is effectively abolished. However, law practitioners should still be able to use a subpoena to notify creditors as to the breach of contract to fulfill legal effort requirements. Second, this paper discusses whether the Constitutional Court Ruling impairs exercise of parate executie in other security rights by comparing it to Supreme Court Ruling Number 3210/K/Pdt/1984, dated 30 January 1986, which impairs the exercise of parate executie in Mortgage, before being remedied by implementing regulation of the Auctioneer Office. Using that approach, the ruling is can be shown to have a chilling effect on the exercise of parate executie. The article ends with the suggestion that further guidance is needed in the form of implementing regulation, both by the Supreme Court or the Auctioneer Office.